A Mobile Computing Framework for Pervasive Adaptive Platforms. (25th December 2011) - Brousse, Olivier; Guillot, Jérémie; Sassatelli, Gilles; Gil, Thierry; Grize, François; Robert, Michel
Abstract : Ubiquitous computing is now the new computing trend, such systems that interact with their environment require self-adaptability. Bioinspiration is a natural candidate to provide the capability to handle complex and changing scenarios. This paper presents a programming framework dedicated to pervasive platforms programming. This bioinspired and agentoriented framework has been developed within the frame of the PERPLEXUS European project that is intended to provide support for bioinspiration-driven system adaptability. This framework enables the platform to adapt itself to application requirements at high-level while using hardware acceleration at node level. The resulting programming solution has been used to program three collaborative robotic applications in which robots learn tasks and evolve for achieving a better adaptation to their environment.